2017
DOI: 10.4013/ctc.2017.101.08
|View full text |Cite
|
Sign up to set email alerts
|

Treinamento em habilidades sociais para usuários de drogas: revisão sistemática da literatura

Abstract: Este é um artigo de acesso aberto, licenciado por Creative Commons Atribuição 4.0 Internacional (CC BY 4.0), sendo permitidas reprodução, adaptação e distribuição desde que o autor e a fonte originais sejam creditados. Resumo.A literatura descreve que usuários de drogas apresentam baixos escores em habilidades sociais e que estas podem ser desenvolvidas através do Treinamento em Habilidades Sociais (THS). Entretanto, carecem de sistematizações sobre tal intervenção no contexto nacional e internacional. Dessa f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 19 publications
0
9
0
9
Order By: Relevance
“…When the ability is only emitted sporadically, it is considered to exist in the repertory, but performance deficits occur. Also, if the individual faces great difficulty in the emission of a certain ability, with absence of spontaneity, the fluency deficit occurs (BARRETO et al, 2011;LIMBERGER et al, 2017). The most commonly used measures are self-report instruments and observational protocols, as well as the identification of acquisition, performance and fluency deficits to assess deficits and/or difficulties in social skills (BARRETO et al, 2011;LIMBERGER et al, 2017).…”
Section: Palavras-chavementioning
confidence: 99%
See 2 more Smart Citations
“…When the ability is only emitted sporadically, it is considered to exist in the repertory, but performance deficits occur. Also, if the individual faces great difficulty in the emission of a certain ability, with absence of spontaneity, the fluency deficit occurs (BARRETO et al, 2011;LIMBERGER et al, 2017). The most commonly used measures are self-report instruments and observational protocols, as well as the identification of acquisition, performance and fluency deficits to assess deficits and/or difficulties in social skills (BARRETO et al, 2011;LIMBERGER et al, 2017).…”
Section: Palavras-chavementioning
confidence: 99%
“…In this sense, social skills training (SST) is one of the main approaches used in the treatment of chemical dependency (SÁ; DEL PRETTE, 2014;SCHNEIDER et al, 2016;COUTINHO et al, 2017;LIMBERGER et al, 2017). Research on the repertory of social skills of users of psychoactive substances can help health professionals to develop strategies and interventions aimed at the care and treatment of users of psychoactive substances.…”
Section: Palavras-chavementioning
confidence: 99%
See 1 more Smart Citation
“…Literature about SST for treatment of drug users is still lacking, according to a systematic review of the literature (Limberger, Trintin-Rodrigues, Hartman, & Andretta, 2017). This review was done on papers from the MEDLINE Complete, Scopus, IBECS, Index Psi, and LILACS databases and brings to light five studies that performed SST with drug users under treatment.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, symptoms of depression, anxiety, and stress can prevent individuals from expressing a socially skilled repertoire, thus negatively impacting their quality of life (Del Prette & Del Prette, 2011). In these terms, because of positive results achieved with SST such as improved social skills and increased treatment adhesion (Limberger et al, 2017) and despite the scarce literature on SST in SUD treatment, the review showed the need for evidence-based interventions to be developed and their effects to be assessed in the context of therapeutic communities. Therefore, the aim of the present study is to describe the results of a pilot study regarding the social skills training of drug users under treatment.…”
Section: Introductionmentioning
confidence: 99%